(untitled) (Indian Journal of Nematology, 2024)
A systematic investigation was undertaken in four districts of Uttar Pradesh to assess the plant parasitic nematode community associated with mango orchards. Eight genera of phytonematodes were encountered viz., Hemicriconemoides mangiferae, Hoplolaimus indicus, Rotylenchulus reniformis, Tylenchorhynchus sp., Helicotylenchus dihystera, Pratylenchus sp., Tylenchus sp. and Meloidogyne incognita. The absolute density of H. indicus was the maximum followed by H. mangiferae. The highest absolute frequency and prominence values was recorded for H. mangiferae followed by H. indicus, while, M. incognita was the least frequent, abundant and prominent species. Sedentary ectoparasitic nematode, H. mangiferae was the most predominant nematode in Lucknow, Unnao and Faizabad districts. M. incognita was recorded only in Faizabad district and Tylenchus sp. was observed in all surveyed districts except Barabanki. The incidence of mango decline is increasing in India and hence the role of nematodes in mango decline needs to be further validated.